Different stakeholders' perceptions and asymmetric influencing factors towards nature-based tourism in Hong Kong. Issue 8 (2nd August 2020) - Zhang, Shuying; Chan, Chung-Shing; Liu, Jiaming; Zhu, He
ABSTRACT: This paper compares nature-based tourism perceptions and influencing factors of local residents ( n  = 216) and inbound tourists ( n  = 225) in Hong Kong. The results reveal that local residents and tourists take divergent attitudes towards basic conditions, social impacts and ecological conservation when they visiting the nature in Hong Kong. By combining psychological expectation (importance) with actual satisfaction (performance), the asymmetric effects of influencing factors are detected. And an asymmetric three factors model is generated to show the changes of influence degree and influence mode on nature-based tourism to provide reference for rationally optimizing management and promoting product quality.